Effects of chlorine and potassium mineral nutrition on the leaf morphology of the PB 121 hybrid coconut palm (Malayan Yellow Dwarf x West African Tall) - I. Mialet-Serra; X. Bonneau (International Coconut Community Journal, 2004)
The effects of chlorine and potassium on the leaf morphology of 6-year-old PB 121 hybrid coconut palms were studied in 1995 and 1996 in southern Lampung (South Sumatra, Indonesia). The parameters considered were frond and leaflet size (length, maximum width, area) and their number. Chlorine and potassium had an exclusive effect on leaflet size, increasing their area. Potassium primarily affected petiole length, hence total frond length. Synergy between these two ions only occurred for the number of leaflets. Chlorine and potassium acted independently on stem diameter and synergistically on height. Coconut palms receiving potassium or chlorine had significantly more voluminous leaf crowns. As time went by, this phenomenon increased despite constant monthly leaf emission. In a situation of equilibrium, the much larger mean crown area and leaf area index of coconuts receiving chlorine and potassium augured well for an earlier start to bearing and higher nut yields.